Engineering dynamics reimagined: a gamified online learning platform - Sahol Hamid, Yazmin; Md Zain, Mohd Raizamzamani; Mohammad Noh, Nurbaiah; Mohamad, Mazlina; Rosli, Nurul Adhlin Ilyana (2025)
Conventional teaching methods in engineering dynamics frequently do not accommodate the varied learning requirements of contemporary digital-native students. This paper presents Dynamics in Life, a gamified web-based learning platform that utilizes digital tools such as Wordwall, Kahoot, and Quizzes to improve student engagement, retention, and conceptual comprehension. The platform incorporates interactive simulations, real-time feedback, adaptive quizzes, and reward-based progress systems, aimed at tertiary learners and pre-university physics students. The platform, grounded in constructivist learning theory and gamification frameworks, targets cognitive and affective learning domains. Following Sustainable Development Goals (SDG 4 and SDG 9), the solution fosters equitable access to more effective STEM education. An evaluation involving 78 students in the initial learning outcome study revealed statistically significant enhancements in understanding and motivation, while a subsequent reflection survey with 222 students provided more profound insights into engagement, development challenges, and SDG awareness. In conclusion, Dynamics in Life demonstrates that gamified, web-based learning can effectively transform the teaching of complex engineering concepts and inspire greater student engagement.